Implications of CI therapy for visual deficit training - Taub, Edward; Mark, Victor W.; Uswatte, Gitendra (Frontiers in Integrative Neuroscience, 2014)
We address here the question of whether the techniques of CI therapy, a family of treatments that has been employed in the rehabilitation of movement and language after brain damage might apply to the rehabilitation of such visual deficits as unilateral spatial neglect and visual field deficits. CI therapy has been used successfully for the upper and lower extremities after chronic stroke, cerebral palsy (CP), multiple sclerosis (MS), other CNS degenerative conditions, resection of motor areas of the brain, focal hand dystonia, and aphasia. Treatments making use of similar methods have proven efficacious for amblyopia. The CI therapy approach consists of four major components: intensive training, training by shaping, a “transfer package” to facilitate the transfer of gains from the treatment setting to everyday activities, and strong discouragement of compensatory strategies. CI therapy is said to be effective because it overcomes learned nonuse, a learned inhibition of movement that follows injury to the CNS. In addition, CI therapy produces substantial increases in the grey matter of motor areas on both sides of the brain. We propose here that these mechanisms are examples of more general processes: learned nonuse being considered parallel to sensory nonuse following damage to sensory areas of the brain, with both having in common diminished neural connections (DNC) in the nervous system as an underlying mechanism. CI therapy would achieve its therapeutic effect by strengthening the diminished neural connections. Use-dependent cortical reorganization is considered to be an example of the more general neuroplastic mechanism of brain structure repurposing (BSR). If the mechanisms involved in these broader categories are involved in each of the deficits being considered, then it may be the principles underlying efficacious treatment in each case may be similar. The lessons learned during CI therapy research might then prove useful for the treatment of visual deficits